2011
DOI: 10.5194/angeo-29-1635-2011
|View full text |Cite
|
Sign up to set email alerts
|

Study of TEC, slab-thickness and neutral temperature of the thermosphere in the Indian low latitude sector

Abstract: Abstract. The ionospheric equivalent slab-thickness is an important parameter which measures the skewness of the electron density profile of the ionosphere. In this paper, the diurnal, seasonal, day-to-day and latitudinal variations of ionospheric parameters namely total electron content (TEC), the peak ionization density of F-layer (NmF2), equivalent slab-thickness (τ ) and neutral temperature (T n ) are presented. The simultaneous data of GPS-TEC and NmF2 from Trivandrum (8.47 • N, 76.91 • E), Waltair (17.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Comparison with the measured T i for corresponding periods indicates that MSISE 90 simulated T n is generally higher than T i during nighttime, while the reverse is true in case of daytime average T i and T n . Venkatesh et al (2011) have found that T n computed from ionospheric slab thickness measurements for the low sunspot years 2004-2005 compare well with MSIS 90 derived temperature over Indian equatorial and low latitudes during daytime hours. A detailed comparative study of the neutral temperature predicted by the MSIS model with ion and electron temperatures measured over the Indian zone will be undertaken and reported in future.…”
Section: Neutral Temperature From the Msis Modelmentioning
confidence: 56%
See 1 more Smart Citation
“…Comparison with the measured T i for corresponding periods indicates that MSISE 90 simulated T n is generally higher than T i during nighttime, while the reverse is true in case of daytime average T i and T n . Venkatesh et al (2011) have found that T n computed from ionospheric slab thickness measurements for the low sunspot years 2004-2005 compare well with MSIS 90 derived temperature over Indian equatorial and low latitudes during daytime hours. A detailed comparative study of the neutral temperature predicted by the MSIS model with ion and electron temperatures measured over the Indian zone will be undertaken and reported in future.…”
Section: Neutral Temperature From the Msis Modelmentioning
confidence: 56%
“…Higher electron energy results in higher ion temperature in the post sunrise period. This morning peak becomes prominent in the low latitude ionosphere due to the vertical E × B plasma drift, which decreases the electron density followed by an increase in T e (Su et al, 1995(Su et al, , 1996Balan et al, 1997). After sunrise, the ion temperature falls as the electron temperature also falls due to sharing of energy with more electrons.…”
Section: Temporal and Latitudinal Variationsmentioning
confidence: 99%
“…However, the GPS signals traverse the dispersed ionosphere carrying its signature, hence offer exceptional opportunities for ionospheric research. Ionospheric TEC from ground-based GPS observations have been investigated widely in the past few decades (Mannucci et al, 1998;Liu et al, 2005;McKinnell et al, 2007;Moeketsi et al, 2007;Opperman et al, 2007;Venkatesh et al, 2011). The GPS satellites orbit at about 20,200 km altitude in 6 orbital planes covering almost whole part of the globe.…”
Section: Introductionmentioning
confidence: 99%
“…For example, one of the most useful parameters which can be investigated using GNSS data combined with ionosonde data is the ionospheric slab thickness (e.g. Jayachandran et al, 2004;Jin et al, 2007;Stankov and Warnant, 2009;Venkatesh et al, 2011). The ionospheric slab thickness (s) is defined as the ratio of the total electron content (TEC) to the F 2 -layer peak electron density (N m F 2 ), where N m F 2 is proportional to the square of the F 2 -layer critical frequency (f o F 2 ).…”
Section: Introductionmentioning
confidence: 99%